PARTISIPASI POLITIK MASYARAKAT DALAM PEMILUKADA 2018 KABUPATEN SINJAI (STUDI KASUS DESA KOMPANG KECAMATAN SINJAI TENGAH KABUPATEN SINJAI) - M Erwin Syukri (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This study aims to determine the political participation of the Kompang village community in the post-conflict local election of Sinjai Regency 2018. The type of research is qualitative, data collection techniques are observation, interview and documentation. The informants consisted of the Kompang Village Head, the Kompang Village PPS Chair, the PPS Members who served in Kompang Village at the time of the 2018 election and the community who knew a lot about research. The data analysis technique was carried out by collecting data, simplifying data, presenting data and drawing conclusions. Based on the results of the research, it can be seen that the political participation of the Kompang village community in the 2018 Sinjai Regency post-conflict local election is a spectator. The political participation of the Kompang Village community in the 2018 Sinjai Regency post-conflict local election was not so apathetic, this is evidenced by almost as a whole the community has exercised their voting rights, even if there is an apathy it is due to compulsion due to busy work carried out outside the village which is far from the village where they voted, such as construction workers, garden workers, fishermen, there are also some residents, some of the residents of Kompang village also work in the sea following their skipper so they don't have time to come to exercise their voting rights. Meanwhile, for the spectator's attitude that is owned by the people of Kompang Village, this is proven by almost all people to use their voting rights, because the majority of people are farmers so most people only use their voting rights but are not involved in politics, the majority of their farmers are more likely to prioritize activities in the garden than political. Meanwhile, gladiatorial behavior is only minimal because gladiator attitudes are usually only from well-respected families such as Karaeng in Kompang Village, these people are still very influential, because the average citizen still sees from social status.